Call To action - Prevention of mother To child transmission of HIV - Ashraf Hassen Coovadia; Ameena Ebrahim Goga; Laurie Schowalter (AOSIS, 2009)
The Prevention of Mother to Child Transmission of HIV (PMTCT)programme is a critical intervention to reduce the incidence of paediatric HIV infections . It is also a key intervention to decrease infant, child and maternal mortality. The optimal implementation of a sound, evidence-based PMTCT programme is essential to meet both the HIV reduction targets in the National Strategic Plan1 and to achieve Millennium Development Goals(MDGs) 4 (reducing infant and child mortality) and 5 (reducing maternal mortalty).2 Since 2001, South Africa has been implementing a programme to prevent mother-to-child transmission of HIV. Since 2007, national PMTCT policy has evolved into a strong, enabling framework that should reduce vertical transmission significantly. This paper reviews the milestone studies that have contributed to our knowledge about drug regimens to reduce MTCT (mother-to-child transmission of HIV), reviews the latest South African PMTCT guidelines and the possible future changes. Strengthened / revised drug regimens for PMTCT are, essential but insufficient for measureable decreases in HIV transmission and improvements in maternal and childl health. The main challenge is implementation. Until the enhanced PMTCT policy is effectively operationalised, measureable achievements will remain elusive.